The works of the Institute of Metallurgy and Metallurgical Sciences at the Warsaw University of Technology, and the person of Jan Czochralski - Mariusz W. Majewski (Studia Historiae Scientiarum)
The article discusses the issues of implementation of important achievements in the field of metallurgy (including armored weapons, fortifications and the navy), under the supervision of prof. Jan Czochralski, who played an important role in the development of the armed forces of the Second Polish Republic.